Exploring Indigenous Feminist Relational Sovereignty: Feminist Conversations, Non-colonizing Solidarities, Inclusive Nations - D'Arcangelis, Carol Lynne (Atlantis, 2010)
This article juxtaposes Indigenous feminist perspectives on sovereignty with related ideas of feminist scholars Jacqui Alexander and Nandita Sharma in order to further feminist theorizations of sovereignty and nationhood that reject neo-liberalism, and to forge a "non-colonizing feminist solidarity" with Indigenous peoples, particularly Indigenous women, in their struggles for self-determination.